2018
DOI: 10.2478/dcse-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Education in Elementary Classrooms: Reported Practices of Alumni from a Pre-Service Teacher Course

Abstract: The article reflects results from a web-based survey of early career teachers who had taken a required, hybrid course focused on sustainability science. Many alumni reported early efforts to integrate sustainability topics and ways of thinking into their K-8 classrooms. Teachers reported modeling of classroom behaviors that promoted sustainability more than implementing sustainability into the curriculum. Read-aloud books and videos were used frequently, suggesting the need for available high quality children’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…As teacher educators, we are critically aware that teachers face many obstacles to EfS once they enter the profession, and will need supports from peers, principals and community members in their work ahead [62]. Further longitudinal work is needed to explore the extent to which the changes described here are short-term, or whether the values, sense of agency, motivation and behavioral shifts described here remain or diminish over time.…”
Section: Discussionmentioning
confidence: 94%
“…As teacher educators, we are critically aware that teachers face many obstacles to EfS once they enter the profession, and will need supports from peers, principals and community members in their work ahead [62]. Further longitudinal work is needed to explore the extent to which the changes described here are short-term, or whether the values, sense of agency, motivation and behavioral shifts described here remain or diminish over time.…”
Section: Discussionmentioning
confidence: 94%
“…This item is seen as one of the main barriers because without proper guidance, it would be difficult for both administrators and educators to understand the concept of sustainable development and apply it in teaching. Merritt et al (2018) also agreed that in recent years, books related to the topic of sustainability at different levels of reading act as important agents in enhancing EFS. Anyolo (2015) clearly stated that the Ministry of Education is responsible for providing teaching and learning materials to ensure effective ESD integration in the curriculum.…”
Section: Resultsmentioning
confidence: 83%
“…Administrator C suggested that educators need to be more creative in the process of teaching and learning. Merritt et al (2018) stated that administrators should encourage educators to introduce ways to develop critical thinking skills among the students to help them solve complicated problems. Generally, Educator E was found to be practising the traditional way of teaching.…”
Section: Resultsmentioning
confidence: 99%
“…The four WOT-strategic, futures, values, and systems thinking-are connected to the key competencies in sustainability and provide an overarching "sustainability education framework" , engaging students with the course content. These WOT help the students to think deeply about the content from different perspectives, imagine various scenarios for the future, and analyze systems in order to strategize how best to initiate change in society (Merritt et al, 2018). The course uses a flipped-learning approach in which content is shared in the course's online component through "digital storytelling" .…”
Section: The Casementioning
confidence: 99%